Energy Balance and Metabolism after Cancer Treatment - Tonorezos, Emily S. (2013)
Unfavorable physiological, biological, and behavioral alterations during and following treatment for cancer may lead to chronic energy imbalance predisposing to a myriad of deleterious health conditions including obesity, dyslipidemia, and the metabolic syndrome. In addition to the cardiovascular and musculoskeletal effects of these conditions, energy imbalance and metabolic changes after cancer treatment can also affect cancer-related morbidity and mortality. To this end, lifestyle interventions such as diet and physical activity are especially relevant to mitigate the deleterious impact of chronic energy imbalance in cancer survivors.